Health Service Utilization among Men who Have Sex with Men (MSM) who Live in Toronto: Secondary Analysis of a Cross-sectional Study - Makoroka, Lydia (My University, 2014)
There is a paucity of research describing patterns of access to health services, specifically HIV services among men who have sex with men (MSM) living in Toronto. To understand whether and how MSM access health services, a secondary analysis of a large survey (implemented in 2006-2008) about HIV vulnerability among MSM was undertaken. Through logistic regression methods, an investigation of factors potentially associated with differential access to health services by MSM and subsequent impact on safer sex practices among MSM was conducted. Most participants reported to have seen a family doctor (65.7%) and a dentist (62.5%). Some reported to have accessed walk-in clinics (34.5%), seen a medical specialist (25.4%), and fewer reported accessing emergency rooms (15.7%). The main factors associated with seeing a family physician were income (Adjusted Odds Ratio (AOR): 1.08, 95% Confidence Interval (CI): 1.02-1.14), age (AOR: 1.03, 95% CI: 1.01-1.05), and HIV status (AOR: 3.46, 95% CI: 1.95-6.14). Having been diagnosed with HIV and with STIs were also associated with seeing medical specialist (AOR: 1.89, 95% CI: 1.07-1.93), and using walk-in clinics (AOR: 2.69, 95% CI: 1.75-4.14) respectively; whereas substance use was associated with access to emergency rooms (AOR: 2.21, 95% CI: 1.27-3.87). Ethno-racial identity was not associated with differential access to any of the health services investigated. In addition, access to health services was not found to be associated with safer sex practices. The small sample size did not allow for in-depth comparison of service use by specific ethnicity. In conclusion, health promotion interventions that target young MSM in lower income bracket should be tested to increase access to family physicians. More research with sufficient, diverse and representative data on ethnicity is needed to better understand factors associated with health service utilization by MSM living in Toronto.